2020
DOI: 10.1159/000510005
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and COVID-19: The Two Sides of the Coin

Abstract: The World Health Organization declared COVID-19, the infectious disease caused by the coronavirus SARS-CoV-2, a pandemic on March 12, 2020. COVID-19 is causing massive health problems and economic suffering around the world. The European Association for the Study of Obesity (EASO) promptly recognised the impact that the outbreak could have on people with obesity. On one side, emerging data suggest that obesity represents a risk factor for a more serious and complicated course of COVID-19 in adults. On the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 25 publications
2
69
0
1
Order By: Relevance
“…The COVID-19 pandemic has highlighted the vulnerabilities of patients with obesity and the necessity of creating better strategies for the management of this chronic disease process [ [24] , [25] , [26] ]. Efforts to address the obesity epidemic will help improve not only overall individual health, but also the health of a society, by having the greatest impact on improving health outcomes in a vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has highlighted the vulnerabilities of patients with obesity and the necessity of creating better strategies for the management of this chronic disease process [ [24] , [25] , [26] ]. Efforts to address the obesity epidemic will help improve not only overall individual health, but also the health of a society, by having the greatest impact on improving health outcomes in a vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging low‐grade chronic inflammation may contribute to the “cytokine storm” in severe COVID‐19 cases (24) and increases the vulnerability to infections as well as to metabolic and cardiovascular complications, such as insulin resistance, type 2 diabetes mellitus, microvascular disorders, or progressive atherosclerosis (25). These diseases are also recognized as risk factors in COVID‐19 (1).…”
Section: Discussionmentioning
confidence: 99%
“…Second, in four of the five studies included, information on height and weight was self-reported. In Switzerland, too, it has already been confirmed that men in particular report being taller than they are (especially with increasing age) and women, on the other hand, assess themselves less heavy (Faeh et al, 2009;Faeh et al, 2008;Vinci et al, 2019a). In both cases this would mean rather under-than overestimation of overweight and obesity levels in our analysis.…”
Section: Discussionmentioning
confidence: 48%
“…The health emergency caused by the COVID-19 pandemic currently diverts attention from the prevention and care of non-communicable chronic diseases, such as obesity, to communicable diseases (Dicker et al, 2020). It is important to focus increasingly on the interlinks between the two pandemics, because obviously in this case a communicable and a non-communicable pandemic are linked.…”
Section: Resultsmentioning
confidence: 99%